Maccera Manurung Multicultural Education and Its Implications for Students in Elementary Schools - Zulfikri Zulfikri; Maksum Maksum (Edumaspul: Jurnal Pendidikan, 2023)
The focus of the problem in this research is how 1) the description of Multicultural Education maccera manurung 2) how the implications of cultural values maccera manurung on elementary school students. The purpose of this study was to determine 1) the description of Multicultural Education maccera manurung 2) the implications of cultural values maccera manurung on elementary school students. The data collection techniques include in-depth interviews, participant observation, and documentation. The data analysis in this research is descriptive, qualitative data analysis. The subjects of this research are traditional leaders, students who have implemented the maccera manurung culture and elementary school teachers in the Kaluppini Customary Area. The results of this study show an overview of the maccera manurung culture in the Kaluppini community and the main values in the maccera manurung procession that have implications for elementary school students. These values are described in the procession of maccera manurung culture, among others: ma'balla (respect for others, empathy, respect for God, cooperation) massajo (responsibility, trust, courage, honesty, discipline, love for the country, order) kasiturutan (togetherness, order, discipline, tolerance, courtesy). The implications of maccera manurung multicultural education for elementary school students in this study were identified in the form of empathy, student character and positive social relationships with others in elementary school students